The Immune System and Aging: A Review (International Journal of Food and Nutritional Sciences, 2022)
Immune senescence refers to age-related cellular and serological alterations in immune responses that influence the process of producing particular responses to foreign and self-antigens. Increasing susceptibility to infectious illnesses, worse vaccine response, and increased incidence of cancer, autoimmune, and other chronic disorders are all signs of the immune system deteriorating with age. The aging process affects both innate and adaptive immune responses; however, the adaptive response seems to be more impacted by age-related immune system alterations. Furthermore, the ethology of several age-related illnesses (atherosclerosis, Alzheimer's disease, osteoporosis, and diabetes) has been linked to a persistent low-grade inflammatory state in the elderly. However, some people reach late years without significant health issues, which is referred to as healthy aging. Immune system dysfunction seems to be reduced in this group, most likely owing to unknown genetic and environmental causes. The goal of this study is to outline what is currently known about how the aging process affects the immune system